Bioactive secondary metabolites with multiple activities from a fungal endophyte - Bogner, Catherine W.; Kamdem, Ramsay S. T.; Sichtermann, Gisela; Matthaeus, Christian; Hoelscher, Dirk; Popp, Juergen; Proksch, Peter; Grundler, Florian M. W.; Schouten, Alexander (Microbial Biotechnology, 2017)
In order to replace particularly biohazardous nematocides, there is a strong drive to finding natural product-based alternatives with the aim of containing nematode pests in agriculture. The metabolites produced by the fungal endophyte Fusarium oxysporum 162 when cultivated on rice media were isolated and their structures elucidated. Eleven compounds were obtained, of which six were isolated from a Fusarium spp. for the first time. The three most potent nematode-antagonistic compounds, 4-hydroxybenzoic acid, indole-3-acetic acid (IAA) and gibepyrone D had LC50 values of 104, 117 and 134 μg ml−1, respectively, after 72 h. IAA is a well-known phytohormone that plays a role in triggering plant resistance, thus suggesting a dual activity, either directly, by killing or compromising nematodes, or indirectly, by inducing defence mechanisms against pathogens (nematodes) in plants. Such compounds may serve as important leads in the development of novel, environmental friendly, nematocides.
CRIS-Team Scopus Importer:2023-04-20